The Effect of Providing Different Natural Feeds on The Growth of Manfish (Pterophyllum scale) - Oktavia, Suma Ardhanna Nova; Firmani, Ummul (Jurnal Biologi Tropis, 2024)
Decorative fish is a significant fishery product since it tends to be finished by exporters, one of the elaborate fish that adjusts to be sent out is manfish on the grounds that it has the excellence of variety and agile developments. The growth of manfish can be influenced by appropriate feed, so this study aims to find out what type of natural feed is suitable for the growth of manfish with artificial feed comparisons (pellets). The treatments used in this study were 100% artificial feed (petet) as control/P0, 100% Daphnia sp as 1/P1 treatment, 100% Tubifex as 2/P2 treatment, and 50% Daphnia sp and 50% Tubifex as 3/P3 treatment. The parameters observed during the study were absolute weight growth, absolute length growth, survival rate,  water quality, and feed conversion ratio. The results showed a treatment that used good natural feed in the long growth of manfish, namely P1 treatment of 100% Daphnia sp feed by showing a figure of 5.27±0.29 cm. The absolute weight growth parameters in good natural feed treatment are P1 treatment of 100% Daphnia sp with a figure of 3.20±0.34 g. The results of the study with feed conversion ratio parameters in natural feed treatment showed the results that P1 treatment experienced high fish appetite because feed needs during the study showed a figure of 11454.02 mg. The lowest survival rate was obtained in the control at 66.67% and the highest survival rate at P1 treatment at 91.67%. The measured water quality parameters are temperature, pH, salinity, and dissolved oxygen which each show numbers in the range of 27-17oC, 00/00, 7-8 and 4-5mg/L.